2021
DOI: 10.1007/s10071-021-01524-1
|View full text |Cite
|
Sign up to set email alerts
|

Kea (Nestor notabilis) show flexibility and individuality in within-session reversal learning tasks

Abstract: The midsession reversal paradigm confronts an animal with a two-choice discrimination task where the reward contingencies are reversed at the midpoint of the session. Species react to the reversal with either win-stay/lose-shift, using local information of reinforcement, or reversal estimation, using global information, e.g. time, to estimate the point of reversal. Besides pigeons, only mammalian species were tested in this paradigm so far and analyses were conducted on pooled data, not considering possible in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…The seal often performed without further errors after a single error at the beginning of a R, which suggests that it used the recent history of reinforcement to guide its behavior in line with conditional discrimination (Williams 1971) or the application of a strategy, as previously discussed. A comparable behavior was documented in macaques, rats, and kea, in contrast to pigeons, in so-called mid-session Rs, in which a R occurs in the middle of the session (Laschober et al 2021;Rayburn-Reeves et al 2017, 2013; whereas pigeons seem to use temporal cues to anticipate the point of R and thus started choosing the alternative stimulus before the actual onset of the R; macaques, rats, and keas respond with a change in response behavior only after having experienced the first error/negative feedback. In contrast to the mentioned mid-session R studies, the current experimental design of Rs starting at variable points in time within the session did not allow the seal to use their well-developed timing abilities (Heinrich et al 2016(Heinrich et al , 2020(Heinrich et al , 2021 to anticipate the point of R, but instead forced the seal to focus on the reinforcement history.…”
Section: Discussionsupporting
confidence: 56%
“…The seal often performed without further errors after a single error at the beginning of a R, which suggests that it used the recent history of reinforcement to guide its behavior in line with conditional discrimination (Williams 1971) or the application of a strategy, as previously discussed. A comparable behavior was documented in macaques, rats, and kea, in contrast to pigeons, in so-called mid-session Rs, in which a R occurs in the middle of the session (Laschober et al 2021;Rayburn-Reeves et al 2017, 2013; whereas pigeons seem to use temporal cues to anticipate the point of R and thus started choosing the alternative stimulus before the actual onset of the R; macaques, rats, and keas respond with a change in response behavior only after having experienced the first error/negative feedback. In contrast to the mentioned mid-session R studies, the current experimental design of Rs starting at variable points in time within the session did not allow the seal to use their well-developed timing abilities (Heinrich et al 2016(Heinrich et al , 2020(Heinrich et al , 2021 to anticipate the point of R, but instead forced the seal to focus on the reinforcement history.…”
Section: Discussionsupporting
confidence: 56%
“…Tightly connected to inhibitory control is the ability to quickly adjust one´s behavior in reaction to changing circumstances. In a recent reversal learning experiment, kea, who have previously waited up to 160 s to exchange a less desirable food reward for a preferred reward (Schwing et al 2017 ), showed highly flexible behavior (Laschober et al 2021 ). Test subjects had to discriminate between two images presented on a touchscreen.…”
Section: Domain Generalmentioning
confidence: 99%
“…The second is that individual birds even of the same species may react very differently to the world and will do so according to individual personality traits [ 81 , 82 ]. There is now plenty of evidence that personality or temperament has a good deal to do with a bird’s reproductive success and overall health [ 60 , 61 , 83 , 84 ]. They can suffer ‘mental’ health issues of varying degrees of severity—the worst of which, in cockatoos (family Cacatuidae), are stages of catatonic immobility and swaying while not attending to any external stimuli [ 27 ].…”
Section: Birds In Captive Environments: Identifying or Avoiding Behavioral Problemsmentioning
confidence: 99%